HUBUNGAN ANTARA KUALITAS IBADAH SHALAT DENGAN KEHARMONISAN KELUARGA - Auliani, Diah; Arini, Aida (Universitas Ahmad Dahlan, 2019)
Praying is something that is done with special words and actions that begin with intention. prayer has the obligatory requirements of Islam, understanding, age, not being menstruated, not handicapped. The family is an institution that exists in the community, which can determine harmony in the community so that the community is very dependent on happiness in the family and harmony in the environment. The family is formed through a marriage. A harmonious family can determine the level of community welfare, because marriage is highly recommended by Islam for those who have been able and meet the conditions. The objectives of the researcher are (1) to describe the quality of prayer worship in Tebuireng Gg Village 1. (2) To describe the harmony of the family in Tebuireng Gg Village 1. (3) To describe the relationship between family harmony with the quality of prayer in Tebuireng Gg 1 village.The research that will be used is a descriptive quantitative expost facto approach that is correlative. The independent and related variables in this study include the Quality of Prayers (X) and Family Harmony (Y). This research was conducted in Tebuireng Gg 1 Hamlet in January-February 2019. The data collection used questionnaires and documentation distributed to each family. Date analysis techniques using hypothesis testing.